Characteristics of PM2.5 in Long Binh Industry Park, Bien Hoa City, Vietnam: Mass Concentrations, Chemical Composition, Source Apportionment, and Health Risk Assessment - Anh Le, Hoang; Duy Linh, Bùi; Thanh Tuan, Nguyen; Thu Huyen, Pham (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1, 2024)
This study aimed to assess the concentration, source, chemical properties, and health risks associated with PM 2.5 in Long Binh ward, Bien Hoa city, Dong Nai province, where there is a large distribution of industrial zones. PM 2.5 samples were collected using a high-volume sampler during both the dry and rainy seasons. The mass concentration of PM 2.5 was determined by Mettler Toledo XS205 , and the chemical properties of eleven heavy metal elements were analyzed using inductively coupled plasma mass spectrometry (ICP-MS; iCAP-RQ, Thermo Science, US) . The migration trajectory of PM 2.5 was determined using the HYSPLIT model. The results showed that the PM 2.5 concentration exceeded the WHO recommended value, while only the PM 2.5 concentration in the dry season exceeded the national standard gia (QCVN 05:2013/BTNMT). Industry, road and non-road transportation activities were identified as the main sources of PM 2.5 . The heavy metal element Cr was found to be the most significant contributor to the chemical composition of fine particles. The health risk assessment revealed that the HI values were lower than 1 in both seasons, indicating a low risk of chronic adverse health effects. However, the TRC values  exceeded the recommended threshold for cancer risk in both the rainy season (10 -4  ± 6,6 x 10 -5 ) and dry seasons (7,9 x 10 -4 ± 5,6 x 10 -4 ).